Transition towards sustainable energy production – A review of the progress for solar energy in Saudi Arabia. Issue 1 (January 2018) - Salam, Mohammad Asif; Khan, Sami A.
The purpose of this study is to understand how one of the most non-renewable countries is acting concerning the global challenge of energy supply vs. resources for energy generation. Saudi Arabia is registering the highest energy consumption per capita in the world with its fastest population growth and the rapid pace of industrialization. Its electricity consumption is expected to be more than doubled by 2025, and the carbon emission is supposed to be on the rise. In that backdrop, Saudi Arabia has taken many steps to shift its dependency from oil to solar, wind and nuclear sources of energy, and plans to secure half of the country's electricity needs from the alternative sources of energy in coming 20 years. The government has announced an ambitious plan to install 41 Giga Watt of solar capacity and invest 108.9 billion by 2032. This exploratory study reviews the steps undertaken in this regard to promote the solar energy initiative as envisaged by the government. This paper discusses the issues and challenges in shifting from oil to solar energy in Saudi Arabia. It documents and discusses the drivers that push Saudi Arabia to adopt solar as an alternative source of energy that can be used to reduce oil dependency and to improve environmental sustainability. A multi-pronged approach involving all stakeholders is the key to success in making the solar project sustainable in Saudi Arabia.